Work and labor relations in the construction industry
1 online resource (xviii, 278 pages)
Keywords: "The need for a skilled, motivated and effective workforce is fundamental to the creation of the built environment across the world. Known in so many places for a tendency to informal and casual working practices, for the sometimes abusive use of migrant labor, for gendered male employment and for a neglect of the essentials of health and safety, the industry, its managers and its workforce face multiple challenges. This book brings an international lens to address those challenges, looking particularly at the diverse ways in which answers have been found to manage safe and productive employment practices and effective employment relations within the framework of client demands for timely and cost-effective project completions. Whilst context, history and contractual frameworks may all militate against a careful attention to human resource issues this makes them even more deserving of attention. Work and Labor Relations in Construction aims to share understanding of best practice in the industries associated with construction and related activities, recognizing that effective work organization and good standards of employee relations will vary from one location to another. It acknowledges the real difficulties encountered by workers in parts of the developing world and the quest for improvement and awareness of some of the worst hazards and current practices. This book is both critical and analytical in approach and seeks to alert readers to the need for change. Aimed at addressing practical issues within the construction industry from a theoretical and empirical standpoint, it will be of value to those interested in the built environment, employment relations and human resource management"--